2019
DOI: 10.5194/amt-2019-442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrieval of Eddy Dissipation Rate from Derived Equivalent Vertical Gust included in Aircraft Meteorological Data Relay (AMDAR)

Abstract: Abstract. Some of the Aircraft Meteorological Data Relay (AMDAR) data include a turbulence metric of the derived equivalent vertical gust (DEVG), in addition to wind and temperature. As the cube root of the eddy dissipation rate (EDR) is the International Civil Aviation Organization standard turbulence reporting metric, we attempt to retrieve the EDR from the DEVG for more reliable and consistent observations of aviation turbulence globally. Using the DEVG in the AMDAR archived from October 2015 to September 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Indeed, this proportionality is often used in meteorology to estimate the dissipation rate from ultrasonic anemometers (e.g. [35]), and similar approaches have been used to measure clear air turbulence using the eddy dissipation rate from aircraft [26,27]. We, therefore, took the proportionality of the fit for the power law relationship (between the power and the frequency (−5/3) as a measure of the turbulent energy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this proportionality is often used in meteorology to estimate the dissipation rate from ultrasonic anemometers (e.g. [35]), and similar approaches have been used to measure clear air turbulence using the eddy dissipation rate from aircraft [26,27]. We, therefore, took the proportionality of the fit for the power law relationship (between the power and the frequency (−5/3) as a measure of the turbulent energy.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear from flying in aircraft that turbulence can cause fluctuations in altitude and body motion. In fact, the clear air turbulence has been estimated using routine measurements of aircraft motion [26] and the variation in vertical acceleration [27]. Similarly, Laurent et al [2] showed that there was a linear relationship between the body accelerations of a single 5 kg golden eagle ( Aquila chrysaetos ) during gliding flight and the atmospheric turbulence (specifically, the body accelerations exhibited power spectra characteristic of turbulence and that increased in proportion to the turbulence intensity).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the good agreement between turbulence estimates from the anemometer measurements, the pilot's scores, reanalysis data and proxy values, gives confidence in our overall approach and demonstrates that simple proxies can be employed to assess turbulence strength at fine scales. Our proxies are similar in concept to those developed for aviation (Kim et al, 2020), demonstrating the widespread utility of measurements derived from onboard accelerometers and pressure sensors.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, this proportionality is often used in meteorology to estimate the dissipation rate from ultrasonic anemometers (e.g. Oncley et al, 1996), and similar approaches have been used to measure clear air turbulence using the eddy dissipation rate from aircraft (Huang et al, 2019, Kim et al, 2020. We therefore took the proportionality of the fit for the power law relationship (between the power and the frequency (-5/3) as a measure of the turbulent energy.…”
Section: Turbulence Estimationmentioning
confidence: 99%
See 1 more Smart Citation